Analisis Unsur STEAM dan Literasi Sains dalam Buku Tematik Siswa Kelas IV pada Tema 3 Peduli Terhadap Makhluk Hidup Muatan Pelajaran IPA SD - Leksita Sari; Irwan Koto (Universitas Bengkulu, 2023)
The study is intended to describe principles of STEAM and science literacy in the thematic book (the fourth student book on the 3rd theme concerned with living creatures' stuffed science ds lessons). This type of research is descriptive research. The objects in this study are the STEAM and science literacy elements that were analyzed and appearing in the fourth-grade student thematic book. Research instruments are STEAM element analysis sheets and science literacy. The data analysis techniques used are descriptive. The percentage category of growing up Used the rater percentage formula of the deal. Research shows that: 1) the STEAM element in the fourth-grade elementary student's thematic book the percentage of the biggest indicator growing is the science element by 40%, mathematics by 26,67%, technology by 10%, art by 10%, and engineering by 6.66%; (2) the science literacy in the fourth-grade elementary student book the most indicator percentage for ever showing up is 100% attitude, competence by 55.56%, context by 26.66%, and knowledge by 38.88%.